Implementing the Principle of the Common Good in Classical and Social Enterprises - Marek, Agnieszka; Kostrzewa, Sylwia; Zadroga, Adam (Verbum Vitae, 2023)
This publication aims to identify similarities and differences in the ways of implementing the principle of the common good in classical (commercial) and social enterprises. Given the differences between social and classical enterprises in terms of their objectives and modes of action, it has to be stressed that the nature of the contribution they make to the common good differs in terms of subject and object. The research is embedded in Catholic social teaching (CST) because this approach presents one of the theoretically and practically richest theories of the common good, and secondly, it allows to discover modern ways of building the common good while respecting centuries of tradition and referring to philosophical classics. The common good principle in the light of CST lets us focus not only on the material but also the transcendental aims of human work and life which lead to more sustainable management. Commercial enterprises strengthen intellectual capital and expand technological and business knowledge. The profit earned by these companies essentially contributes to the good of society (taxes, investment, charity), including employees (bonuses, training). Social enterprises, on the other hand, have the advantage of investing in social capital and thus building a civil society based on mutual trust and support, especially at a local and institutional level. The profit generated by these organisations is a means to achieve social goals and not an end in itself. The results of our research show that both commercial and social enterprises contribute to common good on their own ways but the best results can be achieved when they cooperate and use all of their strengths for building the better future.